Palm Sugar Production and Marketing Assistance in Duampanuae Village, Bulupoddo District: Pendampingan Produksi dan Pemasaran Gula Aren di Desa Duampanuae Kecamatan Bulupoddo Kabupaten Sinjai - Nurul Utami; Jamaluddin Jamal; Muh. Judrah; Firdaus Firdaus (Universitas Lancang Kuning, 2023)
Palm sugar production is an effort to generate people's income, but access to sales is experiencing significant obstacles because the production does not have a label, so there is less interest in buying. Likewise in terms of sales, sales are only centeredon the market. Thus, this condition requires special assistance both in terms of product labeling and marketing. The methods used in this assistance are, 1) Observation, observations are carried out to obtain information regarding the production and sale of palm sugar, 2) Implementation, the form of implementation in this activity is starting from manufacturing, packaging, labeling by giving brands and banners, as well as making Facebook account, 3) Marketing, namely the marketing of palm sugar aims to reach a wider community by marketing it through markets, social media, and Bumdes, 4) evaluation, evaluation is carried out to determine people's interest in buying both before assistance is carried out and after assistance is carried out. The data were analyzed descriptively. The results of this assistance are getting a positive response because they are able to make a big contribution and make high motivation to the people of Duampanuae Village, Bulupoddo District in particular and the people of Sinjai Regency in general. Therefore, mentoring activities really need to be carried out in order to provide understanding, motivation, and provide appropriate solutions for the community